2003
DOI: 10.1152/ajpregu.00535.2002
|View full text |Cite
|
Sign up to set email alerts
|

The kallikrein-kinin and the renin-angiotensin systems have a multilayered interaction

Abstract: Understanding the physiological role of the plasma kallikrein-kinin system (KKS) has been hampered by not knowing how the proteins of this proteolytic system, when assembled in the intravascular compartment, become activated under physiological conditions. Recent studies indicate that the enzyme prolylcarboxypeptidase, an ANG II inactivating enzyme, is a prekallikrein activator. The ability of prolylcarboxypeptidase to act in the KKS and the renin-angiotensin system (RAS) indicates a novel interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 150 publications
(182 reference statements)
3
127
0
4
Order By: Relevance
“…The expression of kallikrein decreased in the kidney after gentamicin (80 mg/kg/day, 7 days) ( Table 4). Kallikrein is a serine protease that cleaves kininogen to produce kinin, a vasoactive and natriuretic peptide (Clements 1989;Schmaier 2003). Kallikrein is produced and secreted in distal nephron segments and has been implicated in the control of sodium and water excretion and the long-term control of arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of kallikrein decreased in the kidney after gentamicin (80 mg/kg/day, 7 days) ( Table 4). Kallikrein is a serine protease that cleaves kininogen to produce kinin, a vasoactive and natriuretic peptide (Clements 1989;Schmaier 2003). Kallikrein is produced and secreted in distal nephron segments and has been implicated in the control of sodium and water excretion and the long-term control of arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 Since BK contributes to the antithrombotic nature of endothelium, we postulated that BKB2R KO (BKB2R ÏȘ/ÏȘ ) mice would be prothrombotic. 15 To our surprise we found that BKB2R ÏȘ/ÏȘ mice have long bleeding times and delayed thrombosis times due to an overexpressed angiotensin receptor 2 (AT 2 R) and elevated NO and prostacyclin levels. These investigations indicate a pathway for thrombosis risk reduction via the plasma kallikrein/kinin and renin angiotensin systems.…”
Section: Introductionmentioning
confidence: 93%
“…Synthesis of the first strand of cDNA was performed using 2 g to 5 g total RNA from heart, kidney, or liver of wild-type or BKB2R ÏȘ/ÏȘ mice as template and 1 L oligo(dT) [12][13][14][15][16][17][18] primer (500 g/mL), following the protocol accompanying the SUPERScript Preamplification System for First Strand cDNA Synthesis (Invitrogen). A 5-L aliquot of the cDNA synthesis reaction was amplified with 300 pmol of gene-specific oligonucleotide primers for the bradykinin B1 receptor (BKB1R; Gene Bank accession no.…”
Section: Cdna Synthesismentioning
confidence: 99%
“…Normal kidney function is due to the proper balance between the KKS and the RAS (Schmaier, 2003). In addition, these systems are involved in renal development and maturation (Shen and El-Dahr, 2006).…”
Section: Renal Levels Of Vasoactive System Components Are Regulated Bmentioning
confidence: 99%